The Association between Knowledge and Attitude of Ergonomic Sitting Position to Sitting Posture and Duration among Medical Students - Gilbert Yavin Sutanto; Hadiyanto Usman; Ignatio Rika Haryono (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: Medical students may spend more time sitting and learning. However, ignorance of the ergonomic sitting position and long sitting duration can lead them to an incorrect sitting position and high sedentary activity. Thus, this study investigated the association between knowledge and attitude towards ergonomic sitting position to sitting duration and posture among medical students. Methods: This cross-sectional study involved 30 students of the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Data were obtained using a questionnaire. Questionnaires were distributed to participants and consisted of 2 parts, the first part included personal data, while the second part contained knowledge, attitude, and practice (sitting duration and posture). Fisher’s exact test and Fisher-Freeman-Halton were applied. The confidence interval was 95%, and the significance level (alpha) was 0.05. Results: 23.3% of the participants have good knowledge about ergonomics sitting position, 40% have adequate knowledge, and 56.7% have a positive attitude towards ergonomics sitting position. 60% of the participants spent sitting time more than 8 hours a day, and 43.3% of the participants had a straight sitting posture. Fisher’s test showed no significant association between ergonomic knowledge and chair sitting duration (p= 0.933) and ergonomic attitude and chair sitting duration (p= 0.711). Fisher-Freeman-Halton exact test showed no significant association between ergonomic knowledge and sitting posture on a chair (p= 0.699) and ergonomics attitude and chair sitting posture (p= 1.000). Conclusions: There was no association between knowledge of ergonomics sitting position with sitting duration and sitting posture and attitude of ergonomics sitting position with sitting duration and sitting posture. Keywords: knowledge – attitude - sitting duration - sitting posture - sitting ergonomics